IoT system for the validation of conditions in shipping couriers - Filipe, P.; Mataloto, B.; Coutinho, C. (2022 International Symposium on Sensing and Instrumentation in 5G and IoT Era (ISSI), 2022)
Online activity has increased over the years and has become a staple in modern society. With it, online shopping businesses have become more common, as well as the number of Internet of Things (IoT) devices. As the shopping experience becomes less personal, some people try to exploit the system causing online businesses to increasingly suffer from return frauds. This paper proposes a solution to this problem, integrating IoT and image processing. The proposed system uses IoT to verify package conditions in courier services, and a database to monitor shipments. The methodology followed for development is described, including the research models, research questions and hypothesis. Development was based on a literature review conducted in order to understand what has been done in the area of logistics services, and what equipment and tools were used for these projects. In addition, the system’s design and architecture are described, giving insight to each components’ function in the system. The system is then implemented to simulate a realworld scenario and tests are carried out. The results of the tests are gathered and analyzed to fine-tune the system. Finally, conclusions are drawn out on the system’s capability of achieving the goals and requirements established before development.